Titanium substrate, water electrolysis electrode, and solid polymer water electrolysis device
A titanium base material with a Magneli phase titanium oxide film addresses corrosion and conductivity issues by promoting reactions and reducing phosphorus contamination, enhancing the performance and durability of water electrolysis electrodes and devices.
Patent Information
- Application Number
- JP2021054473
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-29
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-03-29
AI Technical Summary
Existing titanium base materials used in harsh environments, such as high potential and strong acidic conditions, suffer from insufficient corrosion resistance and conductivity due to the formation of insulating TiO2 films or noble metal coatings, which are costly and can lead to phosphorus contamination in water electrolysis systems.
A titanium base material with a Magneli phase titanium oxide film (Ti n O 2n-1, 4≦n≦10) having a porous structure, high BET value (0.1 m 2/g), and limited phosphorus content (0.1 at% or less) is developed, ensuring excellent conductivity and corrosion resistance, suitable for water electrolysis electrodes.
The solution provides a titanium base material with enhanced conductivity and corrosion resistance, reducing the risk of phosphorus elution and membrane deterioration, enabling cost-effective and durable water electrolysis electrodes and devices.
Smart Images

Figure 0007608930000002 
Figure 0007608930000003 
Figure 0007608930000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a titanium base material having excellent electrical conductivity and corrosion resistance, a water electrolysis electrode formed from the titanium base material, and a solid polymer water electrolysis device. [Background technology]
[0002] Titanium substrates made of titanium or titanium alloys are used as conductive members such as electrodes in applications where oxidation resistance (corrosion resistance) is particularly required. However, when used in severe corrosive environments such as cathode electrodes in polymer electrolyte fuel cells (PEFCs), anode electrodes in water electrolysis equipment, and electrode materials for lithium-ion batteries and lithium-ion capacitors, where there is high potential, the presence of oxygen, or a strongly acidic atmosphere, the corrosion resistance is not sufficient, and an insulating TiO2 film forms on the surface of the titanium base material during use, degrading its performance as a conductive material for electrodes and other devices.
[0003] For this reason, for example, Patent Document 1 proposes forming a coating of a precious metal such as gold or platinum on the surface of a substrate made of aluminum, nickel or titanium, thereby improving corrosion resistance while maintaining electrical conductivity. Furthermore, Patent Document 2 proposes a titanium material in which an oxide film in which no X-ray diffraction peak of TiO2 is observed is formed on the surface of titanium or a titanium alloy. Furthermore, Patent Document 3 proposes a titanium material made of pure titanium or a titanium alloy, which has a titanium oxide layer on the surface thereof, the oxygen to titanium atomic concentration ratio (O / Ti) being 0.3 or more and 1.7 or less, and which has an alloy layer containing at least one precious metal selected from Au, Pt, and Pd formed on the titanium oxide layer.
[0004] However, as shown in Patent Documents 1 and 2, when a precious metal film is formed, the cost increases significantly and it cannot be widely used. Moreover, the oxide film described in Patent Document 3 has insufficient electrical conductivity and corrosion resistance, and therefore cannot be used as a member for use in severe environments.
[0005] Therefore, in Patent Document 4, Ti n O 2n-1 (n is an integer of 1 to 7) is formed on the electrode material. In Patent Document 5, the titanium suboxide coating is represented by the chemical formula Ti n O 2n-1 A titanium substrate has been proposed on which a Magneli phase titanium oxide film made of Magneli phase titanium oxide represented by (4≦n≦10) has been formed. Among titanium suboxides, Magneli phase titanium oxide has the same corrosion resistance as TiO2 and the same electrical conductivity as graphite, and is considered usable even in severe corrosive environments.
[0006] Patent Document 4 discloses the formation of a titanium suboxide film on the surface of a titanium plate by sputtering using a Ti4O7 target and a Ti5O9 target. Patent Document 5 discloses that a TiO2 film is formed by performing plasma electrolytic oxidation in an aqueous solution containing a phosphorus compound, and then this is subjected to microwave plasma reduction treatment to form a Magneli phase titanium oxide coating. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2010-135316 A [Patent Document 2] Patent No. 5831670 [Patent Document 3] JP 2010-236083 A [Patent Document 4] JP 2020-057551 A [Patent Document 5] JP 2019-157273 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, in Patent Document 4, a Magneli phase titanium oxide film or a titanium suboxide film is formed on the surface of a titanium plate by using a sputtering method, which results in a relatively small specific surface area of the film, and there was a risk that the reaction on the electrode surface could not be sufficiently promoted. On the other hand, in Patent Document 5, a TiO2 film is formed by plasma electrolytic oxidation in an aqueous solution containing a phosphorus compound, and then this is reduced to form a Magneli phase titanium oxide film, so that the specific surface area of the Magneli phase titanium oxide film is relatively large.
[0009] However, in Patent Document 5, plasma electrolytic oxidation is performed in an aqueous solution containing a phosphorus compound, so that the Magneli phase titanium oxide film contains phosphorus (P). When a titanium substrate provided with a Magneli phase titanium oxide film containing P is used as an electrode for water electrolysis, there is a risk that P will dissolve during use and deteriorate an ion permeable membrane and the like provided in the water electrolysis cell.
[0010] The present invention has been made against the background described above, and an object of the present invention is to provide a titanium substrate provided with a Magneli phase titanium oxide coating film that is free of P elution and has a large specific surface area, as well as a water electrolysis electrode and a solid polymer water electrolysis device each made of the titanium substrate. [Means for solving the problem]
[0011] In order to solve such problems and achieve the above object, the titanium substrate of the present invention has a substrate body made of titanium or a titanium alloy, and a titanium alloy having a chemical formula Ti n O 2n-1 A Magneli phase titanium oxide coating is formed from Magneli phase titanium oxide represented by the formula (4≦n≦10), and the Magneli phase titanium oxide coating has a BET value of 0.1 m 2 / g, has a porous structure, and is characterized by a phosphorus content of 0.1 at% or less.
[0012] According to the titanium substrate having this configuration, the surface of the substrate body made of titanium or a titanium alloy is provided with a material represented by the chemical formula Ti n O 2n-1 A Magneli phase titanium oxide coating is formed from Magneli phase titanium oxide represented by the formula (4≦n≦10), and the Magneli phase titanium oxide coating has a BET value of 0.1 m 2 / g and has a porous structure, which not only provides excellent electrical conductivity and corrosion resistance but also promotes reactions on the surface of the titanium base material. Furthermore, since the phosphorus content in the Magneli phase titanium oxide film is limited to 0.1 at% or less, it is possible to prevent P from being dissolved during use, and to prevent deterioration of the ion-permeable membrane and the like provided in the water electrolysis cell.
[0013] In the titanium substrate of the present invention, the Magneli phase titanium oxide film preferably contains at least one or both of Ti4O7 and Ti5O9. In this case, since the Magneli phase titanium oxide coating contains at least one or both of Ti4O7 and Ti5O9, which have particularly excellent electrical conductivity and corrosion resistance, it is particularly suitable as an electrically conductive member used in severe corrosive environments such as high potential, the presence of oxygen, and a strongly acidic atmosphere.
[0014] In the titanium base material of the present invention, the thickness of the Magneli phase titanium oxide film is preferably within the range of 0.01 μm or more and 10.0 μm or less. In this case, since the thickness of the Magneli phase titanium oxide film is set to be 0.01 μm or more, sufficient corrosion resistance can be ensured. On the other hand, since the thickness of the Magneli phase titanium oxide film is set to 10.0 μm or less, sufficient electrical conductivity for the titanium base material can be ensured.
[0015] Furthermore, in the titanium base material of the present invention, the base body is preferably a porous body having a porosity in the range of 30% to 97%. In this case, the substrate body made of titanium or a titanium alloy is made porous with a porosity of 30% or more, so that the specific surface area is increased and the reaction on the surface of the titanium substrate can be promoted. Also, the gas generated by the reaction can be efficiently discharged. On the other hand, since the porosity of the substrate body is set to 97% or less, the strength of the substrate body can be ensured.
[0016] The water electrolysis electrode of the present invention is characterized by comprising the above-mentioned titanium base material. The water electrolysis electrode with this structure has the chemical formula Ti n O 2n-1 Since the electrode is made of a titanium substrate on which a Magneli-phase titanium oxide film made of Magneli-phase titanium oxide represented by (4≦n≦10) is formed, the electrode has excellent electrical conductivity and corrosion resistance, and can suppress deterioration due to oxidation, thereby significantly improving the service life. In addition, since the electrode has excellent corrosion resistance, it can be used as a substitute for precious metal electrodes, making it possible to construct water electrolysis electrodes at low cost. Furthermore, the Magneli phase titanium oxide film has a BET value of 0.1 m 2 / g, it is possible to promote the reaction on the electrode surface. Furthermore, since the phosphorus content in the Magneli phase titanium oxide film is 0.1 at% or less, it is possible to suppress the elution of P during use and to suppress deterioration of the ion permeable membrane and the like provided in the water electrolysis cell.
[0017] The solid polymer water electrolysis apparatus of the present invention is characterized by comprising the above-mentioned water electrolysis electrodes. In the solid polymer water electrolysis device with this configuration, the chemical formula is Ti n O 2n-1 Since the water electrolysis electrodes are made of a titanium base material having a Magneli-phase titanium oxide film formed thereon, the Magneli-phase titanium oxide film is represented by (4≦n≦10), and therefore deterioration of the water electrolysis electrodes due to oxidation during use can be suppressed. In addition, there is no need to use precious metal electrodes, and the manufacturing cost of the water electrolysis device can be significantly reduced. Furthermore, the Magneli phase titanium oxide film has a BET value of 0.1 m 2 / g, it is possible to promote the reaction on the electrode surface. Furthermore, since the phosphorus content in the Magneli phase titanium oxide film is 0.1 at% or less, it is possible to suppress the elution of P during use and to suppress deterioration of the ion permeable membrane and the like provided in the water electrolysis cell. Effect of the Invention
[0018] The present invention can provide a titanium substrate provided with a Magneli phase titanium oxide coating that is free of P elution and has a large specific surface area, as well as a water electrolysis electrode and a solid polymer water electrolysis device each made of this titanium substrate. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is an explanatory diagram illustrating an example of a titanium base material according to an embodiment of the present invention. [Diagram 2] FIG. 2 is an enlarged schematic view of a surface layer portion of the titanium base material shown in FIG. [Diagram 3] FIG. 2 is a diagram showing the results of XRD analysis of a titanium oxide film on a titanium substrate according to an embodiment of the present invention. [Figure 4] FIG. 2 is a flow chart showing an example of a method for producing the titanium base material shown in FIG. [Diagram 5] FIG 5 is an explanatory diagram showing the manufacturing process for manufacturing the titanium substrate shown in FIG 1. FIG 5(a) shows the substrate body preparation step S01, FIG 5(b) shows the TiO2 film formation step S02, and FIG 5(c) shows the reduction treatment step S03. [Figure 6] FIG. 1 is a schematic diagram illustrating a solid polymer water electrolysis device including electrodes for water electrolysis according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] BEST MODE FOR CARRYING OUT THE PRESENTLY PREFERRED EMBODIMENTS Hereinafter, a titanium substrate, an electrode for water electrolysis, and a solid polymer water electrolysis device according to embodiments of the present invention will be described with reference to the accompanying drawings.
[0021] The titanium substrate 10 of this embodiment is used, for example, as a conductive member such as a cathode electrode of a polymer electrolyte fuel cell (PEFC), an anode electrode of a water electrolysis device, or an electrode material for a lithium ion battery or a lithium ion capacitor.
[0022] As shown in FIGS. 1 and 2, the titanium substrate 10 of this embodiment includes a substrate body 11 made of titanium or a titanium alloy, and a Magneli phase titanium oxide coating 16 formed on the surface of the substrate body 11.
[0023] In this embodiment, the substrate body 11 is a porous body as shown in FIG. 1, and has a skeletal portion 12 having a three-dimensional mesh structure and a pore portion 13 surrounded by this skeletal portion 12. The porosity P of the substrate body 11 is set to be within a range of 30% or more and 97% or less. The porosity P of the substrate body 11 is calculated by the following formula. P(%)=(1-(W / (V×D T )))×100 W: Mass of the base body 11 (g) V: Volume of the substrate body 11 (cm 3 ) D T : True density (g / cm) of titanium or titanium alloy constituting the substrate body 11 3 )
[0024] In this embodiment, the base body 11 made of this porous body is made of, for example, a titanium sintered body obtained by sintering a titanium sintering raw material containing titanium. The pores 13 surrounded by the skeleton 12 communicate with each other and are open to the outside of the substrate body 11 .
[0025] In the titanium substrate 10 of this embodiment, a Magneli phase titanium oxide film 16 is formed on the surface of the substrate body 11, as shown in FIG. As shown in FIG. 3, the Magneli phase titanium oxide film 16 has the chemical formula Ti nO 2n-1 It is composed of Magneli phase titanium oxide represented by (4≦n≦10). In this embodiment, the Magneli phase titanium oxide film 16 has a porous structure, and the BET value of the Magneli phase titanium oxide film 16 is 0.1 m 2 It is said to exceed / g. In this embodiment, the BET value of the Magneli phase titanium oxide film 16 is 0.2 m 2 / g or more, and 0.3m 2 It is more preferable that the molecular weight is 1 / g or more.
[0026] In this embodiment, the content of elemental phosphorus in the Magneli phase titanium oxide film 16 is set to 0.1 at % or less. In other words, the Magneli phase titanium oxide film 16 contains almost no elemental phosphorus.
[0027] In this embodiment, the Magneli phase titanium oxide film 16 preferably contains at least one or both of Ti4O7 and Ti5O9. The structure of the titanium oxide in the Magneli phase titanium oxide film 16 can be identified by X-ray diffraction analysis (XRD). In addition, the Magneli phase titanium oxide film 16 of this embodiment contains XRD peaks of Ti4O7 and Ti5O9 in X-ray diffraction (XRD), and the sum of the maximum peak intensities of both is greater than the maximum peak intensity of other Magneli phase Ti oxides (6≦n≦10).
[0028] Here, if the thickness t of the Magneli phase titanium oxide film 16 is made thinner, the corrosion resistance decreases but the electrical conductivity improves. On the other hand, if the thickness t of the Magneli phase titanium oxide film 16 is made thicker, the corrosion resistance improves but the electrical conductivity decreases. For this reason, it is preferable to set the thickness t of the Magneli phase titanium oxide film 16 appropriately depending on the properties required for the titanium substrate 10. In this embodiment, in order to sufficiently improve the corrosion resistance, the lower limit of the thickness t of the Magneli phase titanium oxide film 16 is set to 0.01 μm or more. Also, in order to sufficiently improve the electrical conductivity, the upper limit of the thickness t of the Magneli phase titanium oxide film 16 is set to 10.0 μm or less. In order to further improve the corrosion resistance, the lower limit of the thickness t of the Magneli phase titanium oxide film 16 is preferably 0.02 μm or more, and more preferably 0.03 μm or more. On the other hand, in order to further improve the electrical conductivity, the upper limit of the thickness t of the Magneli phase titanium oxide film 16 is preferably 8.0 μm or less, and more preferably 5.0 μm or less.
[0029] The method for producing the titanium base material 10 according to this embodiment will be described below with reference to the flow chart of FIG. 4 and the process diagram of FIG.
[0030] (Base material main body preparation process S01) First, a substrate body 11 made of titanium and a titanium alloy is prepared as shown in Fig. 5(a). In this embodiment, a porous titanium sintered body is prepared as the substrate body 11. The base body 11 made of the porous titanium sintered body can be manufactured, for example, by the following process. A sintering raw material containing titanium is mixed with an organic binder, a foaming agent, a plasticizer, water, and, if necessary, a surfactant to prepare a foamable slurry. This foamable slurry is applied using a doctor blade (applicator) to form a sheet-like molded body. This sheet-like molded body is heated and foamed to obtain a foamed molded body. This is then degreased and sintered. In this way, the base body 11 made of the porous titanium sintered body is manufactured (see, for example, JP 2006-138005 A and JP 2003-082405 A).
[0031] (TiO2 film formation process S02) Next, as shown in Fig. 5(b), the substrate body 11 is anodized in sulfuric acid to form a TiO2 film 26 on the surface of the substrate body 11. In this embodiment, the TiO2 film 26 is formed by a plasma electrolytic oxidation method in which a voltage higher than that of normal anodization is applied in sulfuric acid to generate an arc discharge on the substrate surface and promote oxidation. The concentration of sulfuric acid is preferably in the range of 0.3M to 10.0M. Here, the thickness t0 of the TiO2 film 26 is preferably within a range of 0.01 μm to 10.0 μm.
[0032] (Reduction treatment step S03) Next, the TiO2 film 26 is subjected to a reduction treatment (microwave plasma reduction treatment) using plasma generated by irradiating a gas with microwaves, and the TiO2 film 26 is converted into a TiO2 film having the chemical formula Ti n O 2n-1 The Magneli phase titanium oxide film 16 is made of Magneli phase titanium oxide represented by (4≦n≦10). In this reduction treatment step S03, in order to suppress the diffusion of oxygen to the base body 11 side, the reduction treatment step is performed under conditions of a substrate temperature of 400° C. or less and a treatment time of 15 minutes or less. The lower limit of the substrate temperature in the reduction treatment step S03 can be set to 0° C., and the lower limit of the treatment time can be set to 0.01 minutes.
[0033] In addition, by subjecting the entire TiO2 film 26 to a reduction treatment to form the Magneli phase titanium oxide film 16, the film thickness t0 of the TiO2 film 26 becomes the film thickness t of the Magneli phase titanium oxide film 16. Therefore, by adjusting the film thickness t0 of the TiO2 film 26 in the TiO2 film formation step S02, it is possible to control the film thickness t of the Magneli phase titanium oxide film 16.
[0034] By the above-mentioned manufacturing method, a titanium or titanium alloy is formed on the surface of the substrate body 11, and the surface of the substrate body 11 is coated with a material having the chemical formula Ti n O 2n-1 Thus, a titanium substrate 10 is produced, on which a Magneli phase titanium oxide coating 16 made of Magneli phase titanium oxide represented by (4≦n≦10) is formed.
[0035] Next, a schematic diagram of the water electrolysis electrodes and solid polymer water electrolysis device of this embodiment is shown in Figure 6. The water electrolysis device of this embodiment is a solid polymer water electrolysis device that has high electrolysis efficiency and high purity of hydrogen during generation.
[0036] 6, the solid polymer water electrolysis device 30 of this embodiment includes a water electrolysis cell 31 including an anode 32 and a cathode 33 disposed opposite each other, and an ion permeable membrane 34 disposed between the anode 32 and the cathode 33. Catalyst layers 35, 36 are formed on both sides of the ion permeable membrane 34 (the contact surface with the anode 32 and the contact surface with the cathode 33), respectively. Here, the cathode 33, the ion permeable membrane 34, and the catalyst layers 35 and 36 may be those used in a conventional general solid polymer water electrolysis device.
[0037] The above-mentioned anode 32 is the electrode for water electrolysis of this embodiment. The anode 32 (electrode for water electrolysis) is made of the titanium substrate 10 of this embodiment, and includes a substrate body 11 made of titanium or a titanium alloy, and a Magneli phase titanium oxide film 16 formed on the surface of the substrate body 11. The substrate body 11 is porous, and includes a skeleton 12 with a three-dimensional network structure and pores 13 surrounded by the skeleton 12.
[0038] 6, in the above-mentioned solid polymer water electrolysis device 30 (water electrolysis cell 31), water (H2O) is supplied from the anode electrode 32 side, and electricity is passed through the anode electrode 32 and the cathode electrode 33. Then, oxygen (O2) generated by electrolysis of water is discharged from the anode electrode 32, and hydrogen (H2) is discharged from the cathode electrode 33. As described above, water (liquid) and oxygen (gas) flow through the anode 32, and therefore it is preferable for the anode 32 to have a high porosity in order to stably flow these liquids and gases. In addition, since the anode 32 is exposed to oxygen, it is required to have excellent corrosion resistance. For this reason, the water electrolysis electrode made of the titanium base material 10 of this embodiment is particularly suitable as the anode 32.
[0039] According to the titanium base material 10 of this embodiment having the above-mentioned configuration, the surface of the base body 11 made of titanium or a titanium alloy is coated with a metal oxide having the chemical formula Ti n O 2n-1 The Magneli phase titanium oxide film 16 is formed of Magneli phase titanium oxide represented by (4≦n≦10). The Magneli phase titanium oxide film 16 has a BET value of 0.1 m 2 / g and has a porous structure, the titanium base material 10 has particularly excellent electrical conductivity and corrosion resistance, and can promote reactions on the surface of the titanium base material 10. In the titanium base material 10 of the present embodiment, the phosphorus content in the Magneli phase titanium oxide film 16 is limited to 0.1 at % or less, so that elution of P during use can be suppressed, and deterioration of the ion permeable membrane 34 and the like provided in the water electrolysis cell 31 can be suppressed.
[0040] Furthermore, in this embodiment, the Magneli phase titanium oxide coating 16 contains at least one or both of Ti4O7 and Ti5O9, which are particularly excellent in electrical conductivity and corrosion resistance, as the Magneli phase titanium oxide, and is therefore particularly suitable as an electrically conductive member used in severe corrosive environments such as high potential, the presence of oxygen, and a strongly acidic atmosphere. Furthermore, in this embodiment, the thickness t of the Magneli phase titanium oxide film 16 is set within the range of 0.01 μm or more and 10.0 μm or less, so that it is possible to improve corrosion resistance and electrical conductivity in a well-balanced manner.
[0041] In this embodiment, the base body 11 made of titanium or a titanium alloy is porous, and the porosity P is 30% or more, so that the specific surface area is large and the reaction on the surface of the titanium base 10 can be promoted. Also, the gas generated by the reaction can be efficiently discharged. Therefore, it is particularly suitable as an electrode member. On the other hand, since the porosity P of the porous substrate body 11 is set to 97% or less, the strength of the substrate body 11 can be ensured.
[0042] The water electrolysis electrode (anode 32) and solid polymer water electrolysis device 30 of this embodiment are made of the above-mentioned titanium base material 10, and therefore have particularly excellent electrical conductivity and corrosion resistance, can suppress deterioration due to oxidation, and can significantly improve the service life. In addition, because of its excellent corrosion resistance, it can be used in place of precious metal electrodes, and can form water electrolysis electrodes at low cost. Furthermore, the Magneli phase titanium oxide film 16 has a BET value of 0.1 m 2 / g, it is possible to promote the reaction on the electrode surface. Furthermore, since the content of phosphorus element in the Magneli phase titanium oxide film 16 is 0.1 at% or less, it is possible to suppress the elution of P during use, and it is possible to suppress deterioration of the ion permeable membrane 34 and the like provided in the water electrolysis cell 31.
[0043] Although the embodiment of the present invention has been described above, the present invention is not limited to this, and can be modified as appropriate without departing from the technical concept of the invention. For example, in the present embodiment, the substrate body 11 has been described as a porous body, but is not limited thereto, and may be in the shape of a plate, wire, rod, tube, etc. Also, the substrate body 11 has been described as being made of a titanium sintered body, but is not limited thereto, and a mesh plate, etc. may be used.
[0044] In the present embodiment, the Magneli phase titanium oxide film is described as containing at least one or both of Ti4O7 and Ti5O9, but is not limited thereto. n O 2n-1 It is sufficient that the titanium oxide is made of a Magneli phase represented by (4≦n≦10). Furthermore, in this embodiment, the thickness of the Magneli phase titanium oxide film has been described as being within the range of 0.01 μm or more and 10.0 μm or less, but this is not limited thereto, and it is preferable that the thickness of the Magneli phase titanium oxide film be set appropriately depending on the characteristics required of the titanium base material.
[0045] Furthermore, in this embodiment, the solid polymer water electrolysis apparatus (water electrolysis cell) having the structure shown in FIG. 6 has been described as an example, but the present invention is not limited to this, and water electrolysis apparatus (water electrolysis cell) may have other structures as long as it is provided with water electrolysis electrodes made of the titanium base material of this embodiment. EXAMPLES
[0046] The results of experiments carried out to confirm the effects of the present invention will be described below. First, prepare a substrate body as shown in Table 1. In Table 1, "titanium" refers to pure titanium with a purity of 99.9 mass% or more, and "titanium alloy" refers to a titanium alloy of Ti-0.15 mass% Pd. The dimensions of each substrate body prepared were 50 mm wide x 60 mm long x 0.3 mm thick.
[0047] The porosity of the porous body was calculated by the following formula. P(%)=(1-(W / (V×D T )))×100 W: Mass (g) V: Volume (cm 3 ) D T : True density of titanium or titanium alloy (g / cm 3 )
[0048] Next, a TiO2 film was formed on the surface of the substrate body by the method and conditions shown in Table 1. The thickness of the TiO2 film was set to the value shown in Table 1. In Table 1, for "anodic oxidation (sulfuric acid)", a titanium substrate was placed as a working electrode in the center of a square quartz glass cell filled with 1M sulfuric acid, and 40 mm square Pt meshes were placed on both sides of the titanium substrate as counter electrodes, and anodization was performed under a constant current condition of 3A. In Table 1, for "anodic oxidation (phosphoric acid)", a titanium substrate was placed as a working electrode in the center of a square quartz glass cell filled with 0.3 M phosphoric acid aqueous solution, and 40 mm square Pt meshes were placed on both sides of the titanium substrate as counter electrodes. Anodization was performed at a constant current of 3 A. In Table 1, "air firing" means that a TiO2 film was formed by heating in an air atmosphere under the conditions shown in Table 1. In Table 1, "physical vapor deposition" refers to forming a TiO2 film by sputtering using a sputtering target.
[0049] Next, the substrate body on which the TiO2 film was formed was placed in a microwave plasma reduction device, and the inside of the device was once evacuated to a vacuum (3.8×10 -2 The pressure was reduced to 30 torr (5 Pa or less). Hydrogen gas was then introduced into the apparatus to set the pressure at 30 Pa, and microwaves of 2.45 GHz were irradiated. The reduction time was set to 0.1 to 15 minutes.
[0050] In this manner, a titanium substrate was obtained having a titanium oxide film formed on the surface of a substrate body made of titanium or a titanium alloy. The titanium substrate thus obtained was evaluated for the identification of the titanium oxide film, the BET value, and the P content as follows.
[0051] (Identification of titanium oxide in titanium oxide film) The titanium oxide in the titanium oxide film was identified by X-ray diffraction analysis (XRD). The accelerating voltage was 30 keV, and 8 keV Cu Ka rays were used for the measurement. The measurement range was 2θ = 15° to 35°. The presence or absence of Ti4O7 and Ti5O9 was confirmed by the presence or absence of peaks near 21°, 26°, and 30° (Ti4O7), and 22°, 26°, and 29° (Ti5O9), respectively. The evaluation results are shown in Table 1.
[0052] (BET value of titanium oxide film) After deposition, the sample was cut into square pieces of 2 mm x 2 mm or less, and approximately 0.3 g was placed in a sample holder. The sample holder was placed in a QUANTACHROME AUTOSORB-iQ2 and degassed at a temperature of 200 degrees for 60 minutes. Krypton gas was then introduced and the specific surface area was measured. The evaluation results are shown in Table 1.
[0053] (P content in titanium oxide film) The titanium oxide film was subjected to EDX measurement using an electron microscope (JEOL JCM7000) and the P content was determined by quantitative analysis. The evaluation results are shown in Table 1.
[0054] [Table 1]
[0055] In Comparative Example 1, in which a TiO2 film was formed by anodization in phosphoric acid, the P content in the titanium oxide film having a Magneli titanium phase was 15 at %, which may have deteriorated adjacent members when used as an electrode. In Comparative Example 2, in which a TiO2 film was formed by air baking, it was not possible to form a titanium oxide film having a Magneli titanium phase.
[0056] In Comparative Example 3, in which the TiO2 film was formed by physical vapor deposition, the BET value of the titanium oxide film was 0.1 m 2 / g, resulting in a smaller surface area. In Comparative Example 4, in which no TiO2 film was formed, a titanium oxide film having a Magneli titanium phase could not be formed.
[0057] In contrast, in Example 1-7 of the present invention, in which the TiO2 film was formed by anodization in sulfuric acid, the P content in the titanium oxide film having the Magneli titanium phase was 0.1 at% or less. 2 / g, resulting in a large surface area.
[0058] From the results of the above confirmatory experiments, it was confirmed that according to the present invention, it is possible to provide a titanium substrate having a Magneli phase titanium oxide coating that is free of P elution and has a large specific surface area. [Explanation of symbols]
[0059] 10 Titanium base material 11 Base material body 16 Magneli phase titanium oxide coating 30 Solid polymer water electrolysis device 32 Anode electrode (electrode for water electrolysis)
Claims
1. A substrate body made of titanium or a titanium alloy, The surface of the substrate body is coated with a compound having the chemical formula Ti n O 2n-1 (4≦n≦10) is formed on the surface of the substrate, The Magneli phase titanium oxide film has a BET value of 0.1 m 2 / g, has a porous structure, and has a phosphorus element content of 0.1 at% or less.
2. The Magneli phase titanium oxide film is Ti 4 O 7 Or Ti 5 O 9 2. The titanium substrate according to claim 1, further comprising:
3. 3. The titanium base material according to claim 1, wherein the thickness of the Magneli phase titanium oxide film is within a range of 0.01 μm to 10.0 μm.
4. 4. The titanium base material according to claim 1, wherein the base body is a porous body having a porosity in the range of 30% to 97%.
5. An electrode for water electrolysis, comprising the titanium base material according to any one of claims 1 to 4.
6. A polymer electrolyte water electrolysis device comprising the water electrolysis electrode according to claim 5.
Citation Information
Patent Citations
Method for preparing Magneli-phase titanium oxide mesoporous surface
CN109701510A
Solid-state image pickup device
JP1983031670A
Current collector and battery
JP2010135316A
Titanium electrode material and surface treatment method of titanium electrode material
JP2010236083A
Titanium base material, manufacturing method thereof, electrode for water electrolysis, and water electrolysis device
JP2019157273A